2018
DOI: 10.1080/13561820.2018.1505714
|View full text |Cite
|
Sign up to set email alerts
|

Examining interprofessional team interventions designed to improve nursing and team outcomes in practice: a descriptive and methodological review

Abstract: Effective interprofessional (IP) team-based care is critical to enhance the delivery of efficient care and improve nursing and IP team outcomes. This study aims to review the most recent IP team intervention studies that focused on outcomes related to nursing and IP teams. PubMed, CINAHL, PsycINFO, and Embase were searched for existing literature published between January 2011 and December 2016. The search strategy was developed through both literature review and consultation with a health sciences librarian. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…Neste sentido, resultados de uma revisão integrativa da literatura evidenciaram que, no âmbito da saúde, o trabalho coletivo é visto como instrumento fundamental para aprimorar a prestação de cuidados eficientes, principalmente na área de enfermagem. Reforça-se que a realização do trabalho em equipe melhora os resultados da equipe de enfermagem relacionados aos paciente (10) .…”
Section: Discussionunclassified
“…Neste sentido, resultados de uma revisão integrativa da literatura evidenciaram que, no âmbito da saúde, o trabalho coletivo é visto como instrumento fundamental para aprimorar a prestação de cuidados eficientes, principalmente na área de enfermagem. Reforça-se que a realização do trabalho em equipe melhora os resultados da equipe de enfermagem relacionados aos paciente (10) .…”
Section: Discussionunclassified
“…There is a growing interest worldwide to understand how to improve team functioning and team performance in healthcare settings [1]. Poor team functioning has been identified as a critical factor of adverse events of patient safety [2].…”
Section: Introductionmentioning
confidence: 99%
“…Complex interventions are made of several components and interrelated parts [27,28]. When examining interventions, researchers [1,27] have noted key characteristics to consider included the dose (e.g., duration, frequency), mode of delivery (e.g., written, verbal), and type of intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative studies of the TeamSTEPPS programme have confirmed improvements in teamwork and communication, 22 23 patient safety culture, 24–27 efficiency inpatient care, 24 25 28 complications and mortality, 29 falls 23 and frequency of wrong-site/side/person surgery. 22 Most of the TeamSTEPPS studies are carried out in the USA 30 without any longitudinal follow-up, and there are currently only a few qualitative studies 18 —for example, in surgical and paediatric intensive care 25 and cardiothoracic surgery telemetry. 31 However, a need persists for qualitative studies in surgical ward settings because the team structure in wards is different from that in intensive care unit (ICU) settings; physicians are not situated in the ward for extended periods, thus restricting the possibilities for interprofessional reflections.…”
Section: Introductionmentioning
confidence: 99%